A versaillesi békerendszer geopolitikai következményei - Szilágyi, István (Közép-Európai Közlemények, 2020)
After the first World War the peace- system of Versailles largely reshaped the geopolitical map of Europe and the whole world.Empires disappeared,new succession states and alliance system came into existence.The new world-system developed on the basis of the unjust peace-system that did not consider the right of national self-determination,resulted in instability and included the danger and reality of a new world war to be broken out.These changes and their consequences - having an effect up to now- exercised the influence on the history of Central and Eastern Europe as well.These changes contributed to the development of different branches of social sciences during the period between 1919 and 1939.The theory of international relations and its two tendencies werw elaborated then.